24th Annual European Real Estate Society Conference 2017
DOI: 10.15396/eres2017_157
|View full text |Cite
|
Sign up to set email alerts
|

CEO Overconfidence in Real Estate Markets: A Curse or A Blessing?

Abstract: This paper studies the influence of CEO overconfidence on firms' financial performance and corporate social responsibility (CSR) in the US real estate investment trust (REIT) market.CEO overconfidence has been shown to have both negative and positive influences on firms. This paper is the first to combine the two sides in a single framework. We find that firms with overconfident CEOs tend to have better CSR performance. In addition, better CSR performance can increase firms' financial performance, but this pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Using six Asian Pacific REIT markets, Bao and Li [34] found that market inefficiency amplifies the overconfidence effect amongst investors, particularly during a bull market. Bao and Li [35] also found CSR had a positive impact on US REITs' financial performance, but this influence is undermined by overconfident CEOs. However, the influence of overconfident CEOs on A-REITs remains largely unexplored.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Using six Asian Pacific REIT markets, Bao and Li [34] found that market inefficiency amplifies the overconfidence effect amongst investors, particularly during a bull market. Bao and Li [35] also found CSR had a positive impact on US REITs' financial performance, but this influence is undermined by overconfident CEOs. However, the influence of overconfident CEOs on A-REITs remains largely unexplored.…”
Section: Introductionmentioning
confidence: 98%
“…Although the vast amount of mainstream finance and accounting literature has examined the influence of overconfidence in corporate decision-making and activity, its influence on REITs' corporate decision-making has been largely ignored in the literature. Few exceptions are Eichholtz and Yönder [31], Tan [32], Yung et al [33], Bao and Li [34,35]. Eichholtz and Yönder [31] found that overconfident CEOs do have a discernible impact on US REIT activities.…”
Section: Introductionmentioning
confidence: 99%
“…Managerial self-enhancement biases have consistently been found to affect operational outcomes. With regard to workplace outcomes, overconfidence has been found to be negatively related to firm performance (Chen et al, 2014; Eichholtz and Yönder, 2015), and to moderate the positive relationship between a firm’s corporate social responsibility and its financial performance (Bao and Li, 2017). Contractual motivation, the desire to fulfil one’s obligations, to reciprocate the benefits received from the leader, is likely to be lower among employees whose managers overestimate the quality of their relationship.…”
Section: Introductionmentioning
confidence: 99%